"The Law of the New Hebrides is the Protector of their Lawlessness": Justice, Race and Colonial Rivalry in the Early Anglo-French Condominium. (23rd June 2017) - Stevens, Kate
Abstract : [It] is not I who am on trial here today, but the Law of the New Hebrides. In 1906, Britain and France jointly annexed the New Hebrides. A y-shaped archipelago in the southwest Pacific Ocean, the New Hebrides—which became Vanuatu upon independence in 1980—comprised some eighty islands characterized by high levels of linguistic and cultural diversity. At the moment of annexation, there were also Presbyterian, Anglican, and Catholic missionaries and Euro-American planters and traders, who overlaid religious and national divisions onto the existing social and linguistics ones. Anglo-French rule under the New Hebrides Condominium added a hybrid legal system to this complex mix. During the colonial period, four distinct jurisdictions existed, indicative of the divided, rival nature of governance. These included joint Condominium law, British common law, French civil law, and from 1928, a native code and courts. The plurality and ambiguity of the legal system left ample space for critique and for alternative, extrajudicial justice, as this article explores.